Urgensi Pengembangan Kurikulum Pesantren dalam Meningkatkan Mutu Pendidikan - Asnawan Asnawan (STAIFAS-Press, 2018)
Curriculum development can be done using several approaches. According to Soetopo, there are two types of approaches that can be taken in developing the curriculum, namely the approach that is rooted in the subject matter and approaches that are rooted in the teaching objectives. The first approach is the material-oriented approach to the course. In this approach, the first question arises when compiling a curriculum is what material or material needs to be taught to students. While Hamalik categorizes the curriculum development management approach in six approaches to curriculum development management activities. Keywords: Curriculum Development, Islamic Boarding School, Quality of Education